The effect of digital mathematics learning on students’ problem-solving and creative thinking abilities in statistics learning - Rini Subiyati; Tatag Yuli Eko Siswono; Sendi Ramdhani (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2026)
Digital learning in mathematics has gained increasing attention as a way to support students’ higher-order thinking skills, particularly problem-solving and creative thinking. This study aimed to investigate the effect of digital mathematics learning on students’ problem-solving and creative thinking abilities in statistics. A quasi-experimental design was used involving 54 students who were divided equally into experimental and control groups. Data were collected through pretests and posttests and analyzed using descriptive statistics, paired-sample t-tests, and independent-sample t-tests. The results showed that the experimental group achieved higher posttest scores than the control group in problem-solving ability (72.41 vs. 63.78) and creative thinking ability (70.15 vs. 61.44). The experimental group also showed significant improvement from pretest to posttest in problem-solving ability (mean difference = 15.37, t = 8.21, p < 0.001) and creative thinking ability (mean difference = 14.81, t = 7.56, p < 0.001). In addition, students in the digital learning class performed better than those in the conventional class in fluency, flexibility, originality, and total creativity score. These findings indicate that digital mathematics learning can help students solve statistical problems more systematically and encourage creativity in exploring different solution strategies. This study highlights the importance of integrating digital media, such as interactive videos and Excel-based activities, into statistics learning to support more innovative mathematics instruction.